Factors Affecting Work Fatigue in Nurses at RSU Dr. H. Yuliddin Away Tapaktuan, Tapaktuan District, South Aceh Regency - Pujiono, Tri Prasetyo; Nuraini, Nuraini; Nasution, Ramadhani Syafitri (PROMOTOR, 2024)
The professionalism of a nurse can be seen in carrying out routine work in the field of nursing in accordance with the specified capacity and competence. The performance of nurses in carrying out their duties is not only influenced by the condition of the nurse herself but also influenced by the number of patients being treated, age, gender, facilities and infrastructure, working period, work shifts, body mass index and workload. This type of research uses a descriptive analytical survey with a cross sectional design. The population in this study is 177 people, while the sample is 177 people with a total population technique. Data analysis was carried out by univariate, bivariate and multivariate analysis. The results of this study showed that there was an effect of working period, work shift, body mass index and workload with risk factors for work fatigue in nurses with p-values of 0.014, 0.011; 0.013 and 0.001<0.05. The conclusion of this study is that there is an effect of working period, work shift, body mass index and workload with work fatigue in nurses. It is hoped that the hospital will be able to pay attention to work fatigue in the nurses by providing fitness exercises, educating nurses to stretch, placing younger nurses in the inpatient room, placing male nurses on night shifts, increasing the number of nurses according to the number of treatment beds and replacing administrative tasks with technology.